An Attempt to Find Out the Literacy Genre of Autobiography: Exploring the Complexity of Autobiography as a Literary Genre (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Autobiography holds a place of need, in reality many would state prevalence, among the English literature. These come at the subject from a few viewpoints, recorded and ideological, literary and philosophical, sociological and mental. This decent variety confirms the genre's multifaceted nature, the challenges in characterizing its assortments, and the mines of data and knowledge contained. Much has been said about the literary genre of autobiography. Would it be a good idea for it to try and be seen as a genre? Consistently, numerous endeavors have been made so as to set up a working definition or to choose whether to put autobiographies in the class of fiction or nonfiction.